Creation of nonperturbative horizontal panel of operating table for mobile hospital in the helicopter - Мельник, Виктория Николаевна; Карачун, Владимир Владимирович; Шибецкий, Владислав Юрьевич (Technology audit and production reserves, 2016)
An elastic interaction of angular motion of the helicopter fuselage with the operating table panel is analyzed as the object of research. An urgent surgery for victim immediately after its delivery to the helicopter is made possible through three-axis stabilization of the operating table panel of mobile hospital in the vehicle, in particular, in the form of modular construction in a helicopter. Functional content is based on the use of Petrov two-channel principle for formation of operating table structure that invariant to external disturbances. A mathematical model of mobile hospital is developed and construction accuracy of horizontal panel in a stochastic structure of the angular motion of the helicopter is evaluated. The values of mathematical expectation of the platform drift relative to the stabilization axes are defined. It is recommended to use differential two inertial sensors for each stabilization channel. It is proposed to carry out a further increase in the stabilization accuracy by the introduction of negative feedback on the sum of the sensor signals that are common for two gyroscopes The research results can be used by medical services in conjunction with transport organizations responsible for the maintenance of mobile hospitals. Advantages of two-channel scheme for inertial sensors are in suppressing of the influence of instantaneous values of external disturbances as a stochastic angular motion of the vehicle.